Respuesta :

Answer:

/13=3.60

(a)^2+(b)^2=(c)^2

(6)^2+(3.60)^2=(c)^2

36+13=(c)^2

49=(c)^2

c= /49

c=7

Step-by-step explanation:

pythagorean theorem is (a)^2+(b)^2=(c)^2

then replace it with the given values

inverse of square is squareroot

Answer:

third side is 7 units

Step-by-step explanation:

Hi there!

the Pythagorean theorem is given as a²+b²=c², where a and b are legs (the sides that make up the right angle) and c is the hypotenuse (side that is opposite to the right angle, or in this case, the third side)

we are given the lengths of the 2 legs, and we need to find the hypotenuse

a=6

b=√13

c=unknown value

square the values of a and b, add them together, and set that to equal c squared

or in other words:

6²+(√13)²=c²

36+13=c²

(because 6*6=36; √13*√13=13)

49=c²

√49=√c²

7=c

therefore the hypotenuse is 7 units

Hope this helps!